Nanostructured Zirconia Surfaces Regulate Human Gingival Fibroblasts Behavior Through Differential Modulation of Macrophage Polarization - Wu, Jincheng; Yu, Pei; Lv, Huling; Yang, Shuang; Wu, Zhe (Frontiers in Bioengineering and Biotechnology, 2021)
Zirconia exhibits excellent biocompatibility and is widely used as dental implant materials in prosthodontics. Over the past years research and development of dental implant biomaterial have been focused on osseointegration, but few reports exist regarding the role of immune environment on cellular responses to these materials. The present study investigates the effect of different nanostructured zirconia surface topographies on macrophage phenotypes and their influence on gingival fibroblast behavior. Three different nanostructured zirconia surfaces are characterized using scanning electron microscopy, atomic force microscope and water contact angle. Blank-machined zirconia (BMZ) surfaces were superior to RAW264.7 cell proliferation and adhesion. RAW264.7 seeded on all nanostructured zirconia surfaces polarized towards both inflammatory M1 and anti-inflammatory M2 macrophage with more M2 macrophage phenotype on BMZ surfaces. Meanwhile, conditioned media (CM) from RAW264.7 culture on three nanostructured zirconia surfaces inhibited cells apoptosis to human gingival fibroblasts (HGFs), whereas promoted HGFs proliferation and secretion. Under modulation of RAW264.7 culture, HGFs cultured on BMZ surfaces significantly secreted more extracellular matrix with higher expression of collagen-I (COL-I), vinculin (VCL) and fibronectin (FN) than those on coated self-glazed zirconia (CSGZ) and self-glazed zirconia (SGZ) surfaces. After coated with a nano zirconia film, CSGZ surfaces showed certain changes in cell proliferation, adhesion and protein production compared with SGZ surfaces. These findings will provide an overview of manipulating surfaces topography to modulate macrophage phenotypes in order to create an effective macrophage immune response and reinforce soft tissue integration.